Resident Case Series: Blood Flow Restriction as an Adjunct to Strengthening Exercises in Two Patients with Subacromial Impingement and High Irritability - Angel Ceballos; Giorgio Zeppieri Jr.; Joel Bialosky (International Journal of Sports Physical Therapy)
# Introduction